Current laboratory and clinical practices in reporting and interpreting anti-nuclear antibody indirect immunofluorescence (ANA IIF) patterns: results of an international survey - Van Hoovels L; Broeders S; Chan EKL; Andrade L; Cruvinel WD; Damoiseaux J; Viander M; Herold M; Coucke W; Heijnen I; Bogdanos D; Calvo-Alen J; et al. (BMC, 2022)
Background The International Consensus on Antinuclear Antibody (ANA) Patterns (ICAP) has recently proposed nomenclature in order to harmonize ANA indirect immunofluorescence (IIF) pattern reporting. ICAP distinguishes competent-level from expert-level patterns. A survey was organized to evaluate reporting, familiarity, and considered clinical value of ANA IIF patterns. Methods Two surveys were distributed by European Autoimmunity Standardization Initiative (EASI) working groups, the International Consensus on ANA Patterns (ICAP) and UK NEQAS to laboratory professionals and clinicians. Results 438 laboratory professionals and 248 clinicians from 67 countries responded. Except for dense fine speckled (DFS), the nuclear competent patterns were reported by > 85% of the laboratories. Except for rods and rings, the cytoplasmic competent patterns were reported by > 72% of laboratories. Cytoplasmic IIF staining was considered ANA positive by 55% of clinicians and 62% of laboratory professionals, with geographical and expertise-related differences. Quantification of fluorescence intensity was considered clinically relevant for nuclear patterns, but less so for cytoplasmic and mitotic patterns. Combining IIF with specific extractable nuclear antigens (ENA)/dsDNA antibody testing was considered most informative. Of the nuclear competent patterns, the centromere and homogeneous pattern obtained the highest scores for clinical relevance and the DFS pattern the lowest. Of the cytoplasmic patterns, the reticular/mitochondria-like pattern obtained the highest scores for clinical relevance and the polar/Golgi-like and rods and rings patterns the lowest. Conclusion This survey confirms that the major nuclear and cytoplasmic ANA IIF patterns are considered clinically important. There is no unanimity on classifying DFS, rods and rings and polar/Golgi-like as a competent pattern and on reporting cytoplasmic patterns as ANA IIF positive.